2013
DOI: 10.3389/fimmu.2013.00322
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency in DiGeorge Syndrome and Options for Treating Cases with Complete Athymia

Abstract: The commonest association of thymic stromal deficiency resulting in T-cell immunodeficiency is the DiGeorge syndrome (DGS). This results from abnormal development of the third and fourth pharyngeal arches and is most commonly associated with a microdeletion at chromosome 22q11 though other genetic and non-genetic causes have been described. The immunological competence of affected individuals is highly variable, ranging from normal to a severe combined immunodeficiency when there is complete athymia. In the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 116 publications
0
109
0
Order By: Relevance
“…Restoring a functional thymic stromal environment is expected to provide a long-lasting immune reconstitution [3,4]. In complete DiGeorge syndrome, it has been observed that HSCT did not result in a high-quality immune reconstitution [22,[58][59][60][61].…”
Section: Focus On Therapy and Long-term Outcome: Hsct And Thymus Tranmentioning
confidence: 99%
“…Restoring a functional thymic stromal environment is expected to provide a long-lasting immune reconstitution [3,4]. In complete DiGeorge syndrome, it has been observed that HSCT did not result in a high-quality immune reconstitution [22,[58][59][60][61].…”
Section: Focus On Therapy and Long-term Outcome: Hsct And Thymus Tranmentioning
confidence: 99%
“…Thymic transplantation ideally should be performed immediately after diagnosis of cDGS to facilitate T cell maturation [1]. If it must be delayed, patients may benefit from expansion of prophylaxis to include coverage for mycobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…A minority (<1 %) have complete thymic aplasia, also known as Bcomplete^DGS (cDGS) [1]. Complete DGS is usually defined as <50 naïve (CD45RA + , CD62L + ) CD3 T cells/cc 3 and very low or absent mitogen response [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants born without a thymus require urgent treatment to reconstitute T‐cell immunity 1. Thymus tissue is removed from infants during cardiac surgery, to allow access to the heart.…”
mentioning
confidence: 99%